Interpretasi Makna Uswatun Hasanah Oleh Masyarakat Sarilaba A (Studi Living Qur’an Pada Masyarakat Desa Sarilaba Kecamatan Jawai Selatan) - LUTFI KAMAL; ALKADRI; HADARI (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2025)
This research uses qualitative research methods with a descriptive approach. This research is located in Sarilaba A Village. The steps in data collection include observation, interviews and documentation. Meanwhile, data analysis includes the study of the Living Qur'an and Social Theory. The results of the research show that in Sarilaba A Village we see in society and social interaction, because many of the characteristics of implementing uswatun h}asanah are very important in Sarilaba village. looking at it in terms of speaking, attitude in communicating, carrying out the worship commanded by Allah SWT. Make researchers also look at the development of society in social life, because that is a reflection of the Prophet for all of us and becomes our guide in living this life, so that we are more focused and do not deviate.